Potensi Bahaya dan Resiko Peledakan Terhadap Keselamatan dan Kesehatan Kerja pada Karyawan PT Trimitra Batu Berkah Desa Sempalai Kabupaten Sambas - Nabila, Puteri Asha; Mukhtar, Wahdaniah; Aprillia, Ricka (Universitas Tanjungpura, 2024)
They were blasting at PT. Trimitra Batu Berkah has potential hazards and risks of work accidents due to workers who neglect to use Personal Protective Equipment (PPE), the environment, and unsafe actions. The company has not considered some things such as the completeness of PPE, the provision of drinking water, and the rest period of blasting workers, so an occupational safety and health (K3) management study is needed. The purpose of this study is to identify potential hazards and risks of explosions and recommend control of blasting risks to occupational health safety in employees of PT. Trimitra Blessing Stone Desa Sempalai Kabupaten Sambas. Solving this research problem uses the Job Hazard Analysis method, collecting blasting activity data, identifying potential hazards and risks, analyzing the assessment and risk level of blasting activity, and recommending risk control. The results of the study identified 37 potential hazards and 51 risks in blasting activities, a substantial level of 67% with 34 risks, a priority 3 risk level of 23% with 12 risks, a very high-risk level of 4% with 2 risks, an acceptable risk level of 4% with 2 risks and a priority 1 risk level of 2% with 1 risk. Risk control recommendations were identified as elimination by 5% with 3 controls, substitution by 3% with 2 controls, Engineering by 16% with 10 controls, administration by 28% with 17 controls, and personal protective equipment by 48% with 29 controls.